2021
DOI: 10.1039/d0gc04410e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of dense porous layered double hydroxides from struvite

Abstract: We report an atom economic synthesis of a new type of dense porous layered double hydroxides (S-LDHs) using struvite which is a commonly produced undesirable waste in wastewater treatment plants....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…x/m ÁnH 2 O], where M(II) and M(III) are metal cations in the octahedral positions and A is the anion [17]. The composition can be derived from brucite (Mg(OH) 2 ) by isomorphous substitution of M (II) metal ions to M(III) [18][19][20]. The detailed structure of the LDH is presented in Fig.…”
Section: Basic Features Of Ldhsmentioning
confidence: 99%
“…x/m ÁnH 2 O], where M(II) and M(III) are metal cations in the octahedral positions and A is the anion [17]. The composition can be derived from brucite (Mg(OH) 2 ) by isomorphous substitution of M (II) metal ions to M(III) [18][19][20]. The detailed structure of the LDH is presented in Fig.…”
Section: Basic Features Of Ldhsmentioning
confidence: 99%
“…One of the most often used anionexchange families is the layered double hydroxides (LDHs) in which the positive charges of the double (M 2+ and M 3+ ) metal hydroxide layers were compensated by interlamellar solvated anions. 20,21 These interlayer anions can be further exchanged with more or less difficulties by different type of anions such as amino carboxylates, 22,23 polyoxometallates, 24 Schiff-base complexes, 25 polymeric anions, 26 DNA, 27 etc. In parallel to this process, surface adsorption of the guest molecules could also occur.…”
Section: Introductionmentioning
confidence: 99%
“…To modify 2D ion-intercalated compounds, many different intercalation (wet-) chemical methods have been reported; based on these results, a large number of mixed inorganic or organo-layered composite materials were built up. Through corresponding ion-exchange properties, these compounds can be divided into two groups, i.e., cation- and anion-exchanging materials. One of the most often used anion-exchange families is the layered double hydroxides (LDHs) in which the positive charges of the double (M 2+ and M 3+ ) metal hydroxide layers were compensated by interlamellar solvated anions. , These interlayer anions can be further exchanged with more or less difficulties by different type of anions such as amino carboxylates, , polyoxometallates, Schiff-base complexes, polymeric anions, DNA, etc. In parallel to this process, surface adsorption of the guest molecules could also occur …”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that Pd transferred electrons to Co and Fe in the LDH support, which was evidence of the strong interaction of Pd nanoparticles with the LDH substrate. Besides, four distinct components could be seen in the O 1s spectra for Co 1 Fe 3 –LDH/NF and Pd/Co 1 Fe 3 –LDH/NF (Figure d), including the peak located at around 530.2 eV corresponding to oxygen vacancy (V O ), the peak located at around 530.9 eV appertaining to M–O (M = Pd, Co, Fe), the peak at around 531.6 eV belonging to absorbed H 2 O, and the peak at 532.8 eV corresponding to CO 3 2– , which well matched with those reported LDH materials containing interlayer carbonate anions . The relative area ratios of V O to M–O to H 2 O were about 0.21:1.16:1 for Pd/Co 1 Fe 3 –LDH/NF and 0.35:0.92:1 for Co 1 Fe 3 –LDH/NF, proving that Pd nanoparticles anchored on Co 1 Fe 3 –LDH via O atoms and V O sites.…”
Section: Resultsmentioning
confidence: 54%